2012
DOI: 10.1636/b10-46.1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the thermal micro-environment ofParaphysa parvulaPocock 1903 (Araneae: Theraphosidae), a spider from the Chilean Andes

Abstract: We characterize, in both the laboratory and the field, the preferential thermal microenvironments of Paraphysa parvuia (Pocock 1903) (Araneae: Theraphosidae), a mygalomorph spider that successfully inhabits the high elevation environments of the Chilean Andes. We studied 1 16 spiders. Their average body temperature in the field was 31.02 ± 2.74°C , similar to the laboratory preferred temperature of 31.7 ± 2.31° C, and higher than the ideal temperature of reproductive females, 29.34 ± 2.81° C. In non-reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 20 publications
(29 reference statements)
3
23
0
Order By: Relevance
“…Conduction from the environment, heat transfer by small convection currents and radiation from hot stones all allow spiders to maintain a physiologically appropriate temperature. In this context, the selection of shelters that meet specific temperature conditions appears to be a key condition for the optimization of female reproductive success and the survival of females and juveniles (Schmalhofer, 1999; Canals et al ., 2007; Figueroa et al ., 2010; Veloso et al ., 2012). The species in the present study show preferred temperatures in the range of those reported for other mygalomorph spiders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conduction from the environment, heat transfer by small convection currents and radiation from hot stones all allow spiders to maintain a physiologically appropriate temperature. In this context, the selection of shelters that meet specific temperature conditions appears to be a key condition for the optimization of female reproductive success and the survival of females and juveniles (Schmalhofer, 1999; Canals et al ., 2007; Figueroa et al ., 2010; Veloso et al ., 2012). The species in the present study show preferred temperatures in the range of those reported for other mygalomorph spiders.…”
Section: Discussionmentioning
confidence: 99%
“…Mygalomorph spiders are ectotherm predators that depend upon thermal micro‐environments for energy saving, reproduction and capture of their prey (Greenstone & Bennett, 1980; Humphreys, 1987; Schmalhofer, 1999; Canals et al , 2007; Figueroa et al , 2010; Veloso et al , 2012). However, thermoregulatory behaviour, thermal tolerance and preferred temperatures are only studied in less than 1% of the species of spiders (Humphreys, 1987), and the species that inhabit temperate environments are less well known (Schmalhofer, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Species from different environments typically also have different thermal preferences (Pulz 1987;Schmalhofer 1999) and these may vary seasonally (Schmalhofer 1999), with the breeding season (Hanna & Cobb 2007;Veloso et al 2012) or during the day, as in other ectotherms (Canals et al 1997;Alfaro et al 2013). The election of low temperatures and a relatively narrow range may be explained by phenotypic plasticity as an adaptation to the particular environmental conditions present in Chile.…”
Section: Discussionmentioning
confidence: 99%